Effect of natural antibacterial clays against single biofilm formation by Staphylococcus aureus and Salmonella Typhimurium bacteria on a stainless-steel surface - Wan Omar, Wan Hasyera; Mahyudin, Nor Ainy; Azmi, Nur Naqiyah; Mahmud Ab Rashid, Nor-Khaizura; Ismail, Roslan; Mohd Yusoff, Mohd Hafis Yuswan; Khairil Mokhtar, Nur Fadhilah; Sharples, Gary J. (Elsevier, 2023)
Staphylococcus aureus and Salmonella Typhimurium have a propensity to develop biofilms on food contact surfaces, such as stainless-steel, that persist despite rigorous cleaning and sanitizing procedures. Since both bacterial species pose a significant public health risk within the food chain, improved anti-biofilm measures are needed. This study examined the potential of clays as antibacterial and anti-biofilm agents against these two pathogens on appropriate contact surfaces. Natural soil was processed to yield leachates and suspensions of both untreated and treated clays. Soil particle size, pH, cation-exchange capacity, and metal ions were characterized to assess their importance in bacterial killing. Initial antibacterial screening was performed on nine distinct types of natural Malaysian soil using a disk diffusion assay. Untreated leachate from Kuala Gula and Kuala Kangsar clays were found to inhibit S. aureus (7.75 ± 0.25 mm) and Salmonella Typhimurium (11.85 ± 1.63 mm), respectively. The treated Kuala Gula suspension (50.0 and 25.0 %) reduced S. aureus biofilms by 4.4 and 4.2 log at 24 and 6 h, respectively, while treated Kuala Kangsar suspension (12.5 %) by a 4.16 log reduction at 6 h. Although less effective, the treated Kuala Gula leachate (50.0 %) was effective in removing Salmonella Typhimurium biofilm with a decrease of >3 log in 24 h. In contrast to Kuala Kangsar clays, the treated Kuala Gula clays contained a much higher soluble metal content, especially Al (301.05 ± 0.45 ppm), Fe (691.83 ± 4.80 ppm) and Mg (88.44 ± 0.47 ppm). Elimination of S. aureus biofilms correlated with the presence of Fe, Cu, Pb, Ni, Mn and Zn irrespective of the pH of the leachate. Our findings demonstrate that a treated suspension is the most effective for eradication of S. aureus biofilms with a potential as a sanitizer-tolerant, natural antibacterial against biofilms for applications in the food industry.